2018
DOI: 10.20435/multi.v23i54.1579
|View full text |Cite
|
Sign up to set email alerts
|

Aleitamento Materno Exclusivo e introdução de alimentos industrializados nos primeiros dois anos de vida

Abstract: Objetivou-se identificar a frequência de Aleitamento Materno Exclusivo e a introdução de alimentos industrializados entre crianças com idade inferior a dois anos. Trata-se de estudo transversal, com amostra de conveniência, constituída por 31 mães. 61,3% das mães informaram Aleitamento Materno Exclusivo, por período médio de 4,5 meses, contudo 86,9% e 67,8% das mães ofertaram água e chá, antes dos primeiros seis meses de vida, o que contraria a definição de aleitamento exclusivo. A oferta de alimentos industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
2
0
6
Order By: Relevance
“…Second, Oliveira et al [10] in "Exclusive Breastfeeding and the introduction of industrialized foods in the first two years of life" found that the rate of breastfeeding at or above six months was lower in classes with higher incomes, 10.5% in class C1 (R$2,705) and 5.3% in class C2 (R$1,625). In this research, the rate of children who did not consume breast milk was higher in the groups that received more than three minimum wages (15%), of those that received up to 1 minimum wage (12.20%) and above two to three minimum wages ( 10.98%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, Oliveira et al [10] in "Exclusive Breastfeeding and the introduction of industrialized foods in the first two years of life" found that the rate of breastfeeding at or above six months was lower in classes with higher incomes, 10.5% in class C1 (R$2,705) and 5.3% in class C2 (R$1,625). In this research, the rate of children who did not consume breast milk was higher in the groups that received more than three minimum wages (15%), of those that received up to 1 minimum wage (12.20%) and above two to three minimum wages ( 10.98%).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the consumption of sweetened beverages, it was (6.25%) children from families with incomes above three minimum wages. Oliveira et al [10] found that among children aged 6 to 11 months, the introduction of foods rich in sugar, such as chocolate drinks, soft drinks and artificial juices, was higher in the higher purchasing power classes, with 23.1% B2 (R$4,852), and only 3.3% in the groups that received less than one minimum wage. The consumption of other ultraprocessed foods, such as instant noodles, was prevalent in the groups that received more than one to two wages (6.25%).…”
Section: Discussionmentioning
confidence: 99%
“…O leite materno é descrito como o nutriente ideal para o lactente devido às suas características imunológicas e nutricionais que protegem o recém-nascido de doenças como diarreia, quadros infecciosos e doenças respiratórias, gerando menores custos à família e melhor qualidade de vida ao recém-nascido (RN), dessa forma favorecendo o desenvolvimento neuropsicomotor normal (Oliveira et al, 2018). O aleitamento materno (AM), quando realizado de forma exclusiva, é suficiente e eficaz para manter a demanda nutricional do RN, além de promover o vínculo materno-infantil desde os primeiros momentos da vida (Andrade et al, 2018).…”
Section: Introductionunclassified
“…A amamentação é um processo de profunda interação entre mãe e o bebê que envolve tanto a afetividade quanto repercussões no estado nutricional da criança, fortalecendo a habilidade da mesma na defesa contra infecções, em sua fisiologia, e em seu desenvolvimento cognitivo e emocional, além de gerar benefícios na saúde física e psíquica da mãe (OLIVEIRA RAM, et al, 2018).…”
Section: Introductionunclassified